Antioxidant Properties of Red and Yellow Varieties of Cashew Apple, Nut and Husk (AnacardiumOccidentaleL.) Harvested in Mexico - Figueroa-Valencia M.; Rosales-Martinez P.; Santoyo-Tepole F.; Ramos-Monroy O. A.; García-Ochoa F.; Hernández-Botello M. T.; López-Cortez M. S. (Journal of Antioxidant Activity, 2019)
Numerous studies have reported the health benefits of consuming fruits and vegetables that contain antioxidant properties. Within the group of fruits considered exotic, some are accessible and only consumed in their place of origin, such as soursop, noni, kiwi, pitahaya, and others. Anacardiumoccidentale, cashew, is a crop native to the Brazilian northeast that has excellent medicinal and nutritional properties. Because few studies have characterized cashew produced in Mexico, in the present work, the physicochemical properties and antioxidant capacity of cashew apple (red and yellow varieties) and its nut were studied. The content of total phenolic compounds and the antioxidant capacity were higher in the nut (174.19±20.98 GAE mg/100 g db) while cashew red pulp showed a superior value of the phenol content (159.75±12.91 GAE mg/100 g db) to that of yellow cashew pulp (151.9±5.23 GAE mg/100 g db). A high value was obtained for the TPC of the husk of cashew nut (74.30 mg GAE/g) compared with those of the kernel and false fruit. Red cashew presented a higher antioxidant capacity at 77.65 μmol Trolox/g and was superior to that of the kernel (38.52±2.9 μmol Trolox/g). Because cashew apple is usually discarded, a marmalade based on the pulp is proposed as an alternative for its conservation because it has a high content of phenolic compounds that is conserved for six weeks of shelf life.
Keywords: nut